Efficacy of prone position in acute respiratory distress syndrome: overview of systematic reviews - Michel Marcos Dalmedico; Dafne Salas; Andrey Maciel de Oliveira; Fátima Denise Padilha Baran; Jéssica Tereza Meardi; Michelle Caroline Santos (SciELO, 2017)
Abstract OBJECTIVE To identify and integrate the available scientific evidence related to the use of the prone position in patients with acute respiratory distress syndrome for the reduction of the outcome variable of mortality compared to the dorsal decubitus position. METHOD Overview of systematic reviews or meta-analyzes of randomized clinical trials. It included studies that evaluated the use of prone positioning in patients with acute respiratory distress syndrome published between 2014 and 2016. The AMSTAR tool was used to determine the methodological quality of studies. The GRADE system was used to establish the overall quality of evidence for the mortality outcome. RESULTS From the search strategy, were retrieved seven relevant manuscripts of high methodological quality. CONCLUSION Scientific evidence supports that combined use of protective ventilatory strategy and prone positioning for periods between 16 and 20 hours in patients with acute respiratory distress syndrome and PaO2/FiO2 ratio lower than 150 mm/Hg results in significant reduction of mortality rate.